Attitude towards information privacy issues among students of IIUM - Mohamud, Ibrahim Kalif; Zeki, Akram M.; Saidin, Aznan Zuhid (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The continuous rapid development of ICT will continue to raise new ethical issues and students are likely to have little understanding of the ethical issues associated with using ICT. Thus, the purpose of this research is to explore the attitude of the International Islamic University Malaysia' (IIUM) students' towards information ethics issues of privacy. This study also investigates the differences of the students' individual characteristics of gender, age, marital status, level of study and computer usage with regard to their attitude towards information privacy issues. A total of 219 questionnaires were collected from the undergraduate and graduate students of IIUM who participated in the survey. Students were found to be generally insensitive to the ethicality of information privacy and protecting one's confidential information. There were no significant differences of the students' individuals' characteristics of gender, age marital status and frequency of computer usage with regard to their attitude towards information ethics issues of privacy. However, Level of study showed the existence of significant differences of the students' attitude towards Information Privacy. Revising and updating ethics education courses integrated in the university's curricula can help students develop an ethical responsibility and a proper attitude towards information ethics issues of privacy. In addition, Islamic teachings on ethics embedded in the courses taught can change students' negative attitude towards information privacy.